RAGAM KOMUNIKASI DIKALANGAN SANTRI PADA MASA PANDEMI COVID-19 (Studi Kasus Penggunaan Bahasa Jawa Serang Di Pondok Pesantren Al-Fathaniyah) - Euis Suhartini; Rahmi Winangsih; Nurprapti Wahyu W (Sekolah Tinggi Pariwisata Mataram, 2022)
This study explores several problems in the communication process among students of Al-Fathaniyah Islamic Boarding School, who come from various ethnic backgrounds and different languages. The learning process has become very difficult due to the Covid-19 pandemic situation, where students are required to follow and implement health protocols and implement social distancing. So online learning is one alternative that can overcome this problem. The purpose of this study was to obtain an overview of how the communication process in dealing with learning the regional language (Javanese Serang) as an effort to suppress the spread of Covid-19 at the Al-Fathaniyah Islamic Boarding School, Serang City. This study uses a descriptive qualitative method with a phenomenological approach, while the data collected is through interviews with students through zoom cloud meetings, and face to face with regard to health protocols, by distributing questionnaires to find out how far the variety of student-style communication can run effectively during the pandemic. , while the data analysis was carried out using the theoretical concept of Gerry Philipsen, namely the analysis was carried out interactively, systematically and descriptively